Interaction of amphiphilic derivatives of chitosan with DPPC (1,2-dipalmitoyl-sn-glycero-3-phosphocholine) - de Oliveira Tiera, Vera Aparecida [UNESP]; Winnik, Francoise M.; Tiera, Marcio Jose [UNESP] (Springer, 2010)
The interaction of chitosan and its N-dodecyl and poly(ethylene glycol) derivatives with 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) vesicles was studied to evaluate the influence of molecular architecture of the polymers on the liposomes. The study was carried out in aqueous solution using differential scanning microcalorimetry (DSC) and dynamic light scattering. The interaction of these polymers with DPPC vesicles altered the gel-liquid crystalline phase transition temperature and decreased both the enthalpy (Delta H) and cooperativity of the phase transition. The results obtained indicate that perturbations in the vesicles surface and the incorporation of chitosan and its derivatives into the lipid bilayer upon polysaccharides interaction are responsible for the formation of large vesicles.
Keywords: Microcalorimetry; Liposomes; Modified chitosans; Coating; Vesicle fusion